DEVELOPMENT OF WEB-BASED BASIC ELECTRONIC LEARNING SETS WITH THE APPLICATION OF PROBLEM BASED LEARNING - M. Rahmad; Norazah Mohd Nordin (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
This study was intended to produce a learning sets web-based by the application of problem based learning, as a learning media Basic Electronics on the topic theory and diode circuits. The kind of research used is the ADDIE model with the five steps that is: analysis, design, development model, implementation, and evaluation model. Research instruments that we use is an instrument in the form of validation questionnaire sheets of expert and an instrument practicality namely response users questionnaire. Through this study has been produced a learning shets for the lecture Basic Electronics web-based by the application of problem based learning consisting of the syllabus, lesson plan (LP), module, power point media (ppt) and worksheets for student activities. The learning sets that produced having a level validation of experts to a category valid (score 3.19), the rate of practicality from users the results to a category practical (score 3.20). Based on their own evaluation experts and users, so products learning sets Basic Electronics web-based by the application of the problem based learning announced eligible to be used and developed in lecture on the topic theory and diode circuits in the Physics Education Study Program.